Developing a Commercial Ethics Framework for Analysing Marketing Campaigns - Ribeiro, V.; Vitorino, T.; Dias, Á.; Martinho, D.; Sousa, B. (International Journal of Service Science, Management, Engineering, and Technology, 2022)
This study integrates the relationship of business ethics in marketing campaigns and the importance of the repercussions on organizational performance with the aim of creating a guide of business ethics in marketing campaigns for small and medium enterprises (SMEs). This guide provides SMEs with a tool to analyse their ethical dimension as well as to raise awareness and instil commercial ethics actions in common practice in marketing campaigns in organizations, proving a more detailed approach to global standards. The qualitative methodology has been applied and the proposed theoretical model uses a set of dimensions of ethics, commercial ethics, codes of conduct, marketing, marketing campaigns and SMEs in order to analyse the relationship of commercial ethics with marketing campaigns and its influence on organizations. The results presented demonstrate the influence of commercial ethics on advertising actions; when applied positively, it enables and promotes the brand image, thus contributing to organizational performance, measured by its marketing campaigns. As it is a huge challenge for organizations to ensure commercial ethics in marketing campaigns in its entirety, the proposed model of the guide to commercial ethics in companies, focusing on four thematic areas: commercial ethics, marketing, marketing campaigns and organizational performance.